The Influence of Liquidity, Solvency, and Profitability on Corporate Sukuk Yields: The Role of Sukuk Rating Moderation in Indonesia - Riska, Mila; Nugroho, Lucky (Social and Economic Bulletin, 2024)
The corporate sukuk market in Indonesia is still lagging behind the state sukuk despite the increasing demand for Sharia-based instruments. This phenomenon is caused by the low literacy of investors and issuers related to the issuance of corporate sukuk and the associated risks. This study aims to analyze the influence of liquidity, solvency, and profitability on corporate sukuk yields and examine the role of sukuk rating moderation in this relationship. The study used quantitative methods with multiple regression analysis and Moderated Regression Analysis (MRA), using secondary data from the financial statements of corporate sukuk issuing companies for the 2019-2022 period. The results showed that solvency significantly affected sukuk yield, while liquidity and profitability did not show a significant influence. Sukuk ratings can moderate the influence of liquidity and profitability on yields but do not moderate the influence of solvency. The theoretical implications of this study add to the literature related to corporate sukuk. In contrast, the practical implications guide companies in maintaining solvency and improving sukuk ratings to attract investors. The latest research focuses on corporate sukuk in Indonesia during the 2019-2022 period, which still lacks academic studies.